The Influence of the Ḥamidiyyah Method on Students’ Writing Skill: A Quasi-Experimental Study in a Mahārah Kitābah Class - Rahmawati Rahmawati; Zaimatuz Zakiyah; Ifkar Rasyid; Mamat Rachmat; Sarah Almaulidia (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The declining attention of both instructors and students to the calligraphic dimension of Arabic script has significantly limited learners’ ability to write accurately and efficiently. As calligraphy plays a vital role in mahārah kitābah (Arabic writing proficiency), this study investigates the effectiveness of the Ḥamidiyyah method in improving students’ Arabic writing skills. Using a quasi-experimental design with a non-equivalent control group, the research involved 46 English Education students assigned to experimental and control groups based on consistent attendance across five kitābah sessions. Data were collected through observation, interviews, writing assessments, and documentation, and analyzed using an independent sample t-test. Findings show a statistically significant improvement in the post-test scores of the experimental group, affirming the pedagogical strength of the Ḥamidiyyah method. Additionally, increased engagement and enthusiasm in class suggest that the method enhances not only structural proficiency but also learner motivation. This study supports the integration of traditional calligraphy methods into modern Arabic pedagogy and encourages further exploration of its long-term cognitive and aesthetic impacts.